SISTEM PELAYANAN ON-LINE PADA ASOSIASI INKINDO BENGKULU - Yesi Susanti; Siswanto Siswanto; Yupianti Yupianti (Jurnal Media Infotama, 2015)
The research aims to create a Service System at Bengkulu INKINDO Association. Where the data files on the draft Association Bengkulu INKINDO namely design, Home File, File Gallery, File News, File Propyl, File Member, Guest Files and File Admin. From the discussion can be concluded that in the Making System On-Line Services in INKINDO Bengkulu Association for using weaknesses in the input data can be resolved quickly and precisely and can improve the efficiency and effectiveness of the work in Bengkulu INKINDO Association and the results can be seen on the site www.inkindobengkulu.rumahweb.orgKeyword: Service System, Inkindo